Discrimination of spatial relations and features in faces: effects of inversion and viewing duration. - Barton, Jason J. S.; Keenan, Julian P.; Bass, Trevor (British Journal of Psychology, 2001)
We studied discrimination of changes in eye position, mouth position, and eye colour at viewing durations ranging from 1 second to unlimited time. With upright faces, perception was rapid and did not improve above 2 seconds of viewing time. Face inversion impaired discrimination of mouth position significantly, eye position slightly, but not eye colour. The ‘inversion effect’ for mouth position decreased with increasing stimulus duration, and disappeared when the subject knew that the only change in a trial was in mouth position. A subsequent experiment showed that the inversion impairment in the mouth region was not specific to spatial position but affected mouth colour to a lesser degree. When the mouth region was made more salient by increasing the frequency of mouth change trials, the inversion effect for mouth position decreased, and correlated with an increase in inversion effect for eye position but not eye colour. We conclude that the dominant effect of face inversion upon perception is decreased discrimination in less salient facial regions, that this impairment lessens with increasing viewing time, and that it affects both features and their spatial relations, though the effect on the latter is greater. These results are consistent with greater dependence on a serial component search strategy in inverted faces. Reprinted by permission of the publisher.